Learning Religious Tolerance in Pai Subjects at Ma'arif Bandung High School and Muhammadiyah 3 Plus Bandung High School - khambali, khambali; Supiana, Supiana; Erihadiana, Mohamad; Jaenudin, Mohamad (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study explores the implementation of religious tolerance education in the subject of Islamic Religious Education (PAI) at Ma'arif Bandung High School and Muhammadiyah 3 Plus Bandung High School. The purpose of this study is to analyze how religious tolerance is incorporated into Islamic religious education and school activities, identify strategies used to promote tolerance among students, and evaluate the effectiveness of these methods in fostering an inclusive and harmonious school environment. Using a qualitative descriptive-analytical approach, this study examines how religious tolerance is integrated into the curriculum, teaching methods, and school culture in two institutions affiliated with the two largest Islamic organizations in Indonesia, namely Nahdlatul Ulama (NU) and Muhammadiyah. The data collection methods used were surveys, interviews, observations, and document analysis. The research findings show that although neither school has a specific subject on religious tolerance, tolerance values are instilled in the Islamic Religious Education and Character Education (PAIBP) curriculum through specific themes and learning objectives. In addition, school activities, local curricula such as Aswaja (NU) and Kemuhammadiyahan (Muhammadiyah), and extracurricular programs further strengthen religious tolerance among students. The results of the study highlight that both schools have successfully integrated tolerance education through character-building activities and thematic lessons, fostering an environment of mutual respect among students. However, there are still challenges, especially in providing structured models for teachers to effectively teach religious tolerance.